Retention of placenta on physiological, hematological, biochemical and endocrinological profiles in crossbred cows under tropical island ecosystem - PERUMAL, P; RAVI, S K; DE, A K; BHATTACHARYA, D; ALYETHODI, R R; MUNISWAMY, K; SUNDER, JAI; KUNDU, A (The Indian Journal of Animal Sciences, 2021)
A study was carried out to assess the effect of retention of placenta (ROP) on hamatological, physiological, antioxidant and endocrinological profiles in crossbred cows under tropical island ecosystem of Andaman and Nicobar Islands. Each six number of cows was selected which were affected with ROP as group 2 and without ROP as group 1. These cows were in same parity in same locality with similar type management. Both the group of cows delivered healthy live calves normally and the cases were diagnosed as ROP when it failed to expel after 24 h of parturition. The ROP was removed manually as per standard procedure with aseptic measures. These affected cows were treated successfully and allowed to nurse the calves. Physiological profiles such as rectal temperature (RT), pulse rate (PR), respiratory rate (RR) and skin temperature (ST) were measured. Blood samples were collected, analysed for hematological profiles and serum separated, analysed the antioxidant profiles such as catalase (CAT), superoxide dismutase (SOD), glutathione (GSH), total antioxidant capacity (TAC) and free radical such as malondialdehyde (MDA) and hormone profiles such as estradiol 17β (E2), progesterone (P4) and cortisol (CORT) were estimated. The result revealed that the crossbred cows of ANI with ROP suffered severe anaemia. The ROP affected animals were shown significantly low level of antioxidant profiles and higher MDA level than the unaffected animal groups. Similarly endocrinological profiles revealed the affected animals were having significantly higher level of CORT, P4 and lower level of E2 than unaffected crossbred cows. It was concluded that the ROP in the present study was due to anaemia, lack of antioxidants, over production of free radicals and disturbances of endocrinological profiles.